Policy Implementation Analysis of SPM Health Sector for Hypertension Sufferers in South Kalimantan Province, Indonesia in 2022 - Dewi, Anggi Asri Rusliana; Ayuningtyas, Dumilah (UI Scholars Hub, 2023)
Hypertension is a major cardiovascular risk factor that causes disability throughout the world and among those who are not aware of their health condition, it is often referred to as the silent killer . The prevalence rate of hypertension in Indonesia is quite high. Based on Riskesdas (2018), South Kalimantan Province shows the highest prevalence of hypertension, but the percentage of hypertension sufferers who receive health services is still low. Banjarbaru City has the lowest percentage, namely 11.3% of the target of 100%. Health services for hypertension sufferers are included in the Minimum Service Standards (SPM) for the Health Sector which are regulated in statutory regulations and government policies. The aim of this research is to analyze the implementation of the SPM policy in the health sector for hypertension sufferers in Banjarbaru City. Qualitative research with a Rapid Assessment Procedure (RAP) research design was conducted from May to June 2023 in Banjarbaru City, South Kalimantan Province. Data collection was carried out through in-depth interviews, observation and document review. The results of the research show that the implementation of the hypertension SPM policy has not been optimal, as can be seen from the SPM achievement report in the health sector in Banjarbaru City which is in the lowest position among 12 types of basic health services. In conclusion, several obstacles in the implementation of SPM for hypertension are recording and reporting hypertension sufferers, low public awareness of carrying out examinations and treatment at community health centers so that the data is not recorded, there is no special budget allocation for SPM for hypertension at community health centers, and the dual duties of health workers so that they are not optimal in achieve a program. Cross-sector collaborative efforts are needed for integrated recording and reporting of hypertensive patient data, submission of hypertension SPM budgets, efforts to invite the community, and fair distribution of tasks for community health center officers.